Randomised phase II study to optimise melphalan, prednisolone, and bortezomib in untreated multiple myeloma (JCOG1105). (24th June 2020) - Maruyama, Dai; Iida, Shinsuke; Ogawa, Gakuto; Fukuhara, Noriko; Seo, Sachiko; Miyazaki, Kana; Yoshimitsu, Makoto; Kuroda, Junya; Tsukamoto, Norifumi; Tsujimura, Hideki; Hangaishi, Akira; Yamauchi, Takahiro; et al.
Summary: We conducted a randomised phase II study to determine the optimal dose and schedule of melphalan, prednisone, and bortezomib (MPB) (jRCTs031180097). Transplant‐ineligible untreated multiple myeloma patients were randomised to Arm A (twice weekly bortezomib in one six‐week cycle followed by eight five‐week cycles of four times once weekly bortezomib with melphalan and prednisolone on days 1–4) or Arm B (nine four‐week cycles of three times once weekly bortezomib with melphalan and prednisolone on days 1–4). The primary end‐point was complete response (CR) rate. Of 91 patients randomised to two arms, 88 were eligible. The median cumulative bortezomib doses were 45·8 and 35·1 mg/m 2, CR rate was 18·6% [95% confidence interval (CI) 8·4–33·4] and 6·7% (95% CI 1·4–18·3), and the median progression‐free survival (PFS) was 2·5 and 1·4 years in Arms A and B [hazard ratio (HR) 1·93 (95% CI 1·09–3·42)], respectively. Frequent grade ≥3 haematologic toxicities in Arms A and B were neutropenia (64·4% vs. 28·3%) and thrombocytopenia (35·6% vs. 10·9%). Grade 2/3 peripheral neuropathy was observed in 24·4/2·2% in Arm A and 8·7/0% in Arm B. In conclusion, Arm A was the more promising regimen, suggesting that the twice weekly schedule of bortezomib in the first cycle and higher cumulative dose of both bortezomib and melphalan influences the efficacy of modified MPB.